SEMANTIK INKUISITIF ‘BAGAI MUSANG BERBULU DOMBA’ DALAM PERIBAHASA: STUDI PERBANDINGAN MAKNA DAN FUNGSI - Megasari, Ferika; Otavian, Novriadi; Hermandra, Hermandra (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
The proverb "like a weasel in sheep's clothing" is a linguistic expression rich in cultural values and often used to implicitly criticize hypocrisy. This background prompts the need for a more in-depth analysis of its meaning. The focus of this research is to explore the potential implicit meaning, communicative function, and cultural resonance of this proverb using an inquisitive semantic framework, which views meaning as a trigger for questioning and interpretation. As a crucial step, this study applies descriptive qualitative methods accompanied by comparative analysis across languages—including English, Arabic, Mandarin, and German—to test the universality of the concept. Key findings indicate that the semantic structure of "a predator in disguise" is a universal concept reflecting global ethical concerns about deception and betrayal. Pragmatically, this proverb functions as an effective indirect speech act to convey social criticism in a subtle yet incisive manner. In conclusion, this proverb is not simply an aesthetic form of language, but a dynamic rhetorical instrument and an important means of shaping social consciousness, whose meaning is not only propositional but also open to interpretation by its listeners. ABSTRAKPeribahasa "bagai musang berbulu domba" merupakan ekspresi linguistik yang kaya akan nilai budaya dan sering digunakan untuk mengkritik kemunafikan secara tersirat. Latar belakang ini mendorong perlunya analisis makna yang lebih mendalam. Fokus penelitian ini adalah untuk menggali potensi makna implisit, fungsi komunikatif, dan resonansi budaya dari peribahasa tersebut dengan menggunakan kerangka semantik inkuisitif, yang memandang makna sebagai pemicu pertanyaan dan interpretasi. Sebagai langkah penting, penelitian ini menerapkan metode kualitatif deskriptif yang disertai analisis komparatif lintas bahasa—mencakup Inggris, Arab, Mandarin, dan Jerman—untuk menguji universalitas konsepnya. Temuan utama menunjukkan bahwa struktur semantik "predator yang menyamar" merupakan konsep universal yang mencerminkan kekhawatiran etis global terhadap penipuan dan pengkhianatan. Secara pragmatis, peribahasa ini berfungsi sebagai tindak tutur tidak langsung yang efektif untuk menyampaikan kritik sosial secara halus namun tajam. Kesimpulannya, peribahasa ini bukan sekadar bentuk estetika bahasa, melainkan instrumen retoris yang dinamis dan sarana penting dalam membentuk kesadaran sosial, yang maknanya tidak hanya bersifat proposisional tetapi juga membuka ruang interpretasi bagi pendengarnya.